Trends of infant vaccination timeliness and completion in selected urban slum communities in Ibadan, Southwestern Nigeria: A four-year review (2023)
Background Suboptimal infant vaccination is common in Nigeria and multiple interventions have been deployed to address the situation. Child health indicators are reported to be worse in urban slums compared with other urban areas, but urban data are usually not disaggregated to show these disparities. Examining the timeliness and completion of infant vaccination in urban slums is important to determine the effectiveness of existing interventions in improving infant vaccination among this vulnerable population. This study explored the trends of infant vaccination in selected urban slum communities in Ibadan, Southwest Nigeria between November 2014 and October 2018. Methods This was a cross sectional study where infant vaccination data were extracted from the immunization clinic records of six primary health care centers that were providing infant vaccination services for seven urban slum communities. Data was analyzed using descriptive statistics and Chi square test at α = 05. Results A total of 5,934 infants vaccination records were reviewed, 2,895 (48.8%) were for female infants and 3,002(50.6%) were from Muslim families. Overall, only 0.6% infants had both timely and complete vaccination during the four years under study. The highest number of infants with timely and complete vaccination were seen in 2015(12.2%) and least in 2018 (2.9%). Regarding timeliness of the vaccines, BCG, was the least timely among the vaccines given at birth and the pentavalent and oral polio vaccines’ timeliness reduced as the age of the infants increased. Both yellow fever and measles vaccines were timelier than th(12.1%). Those from Muslim families significantly had delayed and incomplete vaccinations compared with those from Chrisitan families (p = 0.026). Conclusion Infant vaccinations were significantly delayed and incomplete in the study communities during the years reviewed. More focused interventions are required to ensure optimal vaccination of the infants. epentavalent vaccines. Vaccines were most timely in 2016(31.3%) and least timely in 2018